A dysprosium single molecule magnet outperforming current pseudocontact shift agents. Issue 20 (6th May 2022) - Santana, Francielli S.; Perfetti, Mauro; Briganti, Matteo; Sacco, Francesca; Poneti, Giordano; Ravera, Enrico; Soares, Jaísa F.; Sessoli, Roberta
Abstract : A robust dysprosium(iii ) single molecule magnet with large uniaxial magnetic anisotropy induces pseudocontact shifts at almost doubled distance compared to standard shift agents. Abstract : A common criterion for designing performant single molecule magnets and pseudocontact shift tags is a large magnetic anisotropy. In this article we present a dysprosium complex chemically designed to exhibit strong easy-axis type magnetic anisotropy that is preserved in dichloromethane solution at room temperature. Our detailed theoretical and experimental studies on the magnetic properties allowed explaining several features typical of highly performant SMMs. Moreover, the NMR characterization shows remarkably large chemical shifts, outperforming the current state-of-the art PCS tags.